2013
DOI: 10.1093/rheumatology/ket354
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of validity of the self-administered comorbidity questionnaire in patients with ankylosing spondylitis

Abstract: The SCQ is a promising instrument to determine comorbidities and to understand the impact on health outcomes in patients with AS. Excluding rheumatic conditions from the SCQ (mSCQ) improved validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…Supplementary Table 2 (available in the online version of this article at http:// onlinelibrary.wiley.com/doi/10.1002/acr.22573/abstract) shows the patient and study characteristics of the included studies as well as work outcomes reported in the included studies. Of the 25 studies, 22 were crosssectional (1,(5)(6)(7)(8)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 1 case-control (2), and 2 longitudinal (36,37). Different terminology was used to define work status.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Table 2 (available in the online version of this article at http:// onlinelibrary.wiley.com/doi/10.1002/acr.22573/abstract) shows the patient and study characteristics of the included studies as well as work outcomes reported in the included studies. Of the 25 studies, 22 were crosssectional (1,(5)(6)(7)(8)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 1 case-control (2), and 2 longitudinal (36,37). Different terminology was used to define work status.…”
Section: Resultsmentioning
confidence: 99%
“…Medical comorbidity is measured using an adapted and simplified version of the Self‐Administered Comorbidity Questionnaire (SCQ‐18), where higher scores indicate a more severe comorbidity profile.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of extraarticular manifestations (uveitis, psoriasis, and inflammatory bowel disease [IBD]) and of comorbidities was retrieved from the medical records. In order to represent in the analyses the influence of comorbidities on work outcome, the Rheumatic Disease Comorbidity Index (RDCI) was calculated (range 0–9), representing the weighted sum score of common comorbidities (lung disease, diabetes mellitus, hypertension, myocardial infarction, stroke, other heart disease, cancer, fracture [spine, hip, or leg], gastrointestinal ulcer, other gastrointestinal problems, and depression) . In addition, patients underwent clinical examination, which allowed calculating the Bath Ankylosing Spondylitis Metrology Index (BASMI) to assess spinal mobility .…”
Section: Methodsmentioning
confidence: 99%